Effect of heterogeneous tar condensation on coking pressure dynamics – Qualitative numerical analysis. (15th September 2020) - Polesek-Karczewska, Sylwia; Kardaś, Dariusz; Wardach-Święcicka, Izabela
Abstract: Having regard to the practical role of predicting the peak pressure generation inside a coke oven and the demand for recognizing the factors affecting the pressure levels, the transient one-dimensional of thermal and flow processes in a coke oven charge was developed. Tar clogging the cavities between coal particles is considered a factor additional to low permeability of softened coal that may have an effect on pressure increase, however not yet enough described. In order to analyze this issue, the phase transition of heavier pyrolysis gas components was accounted for in the proposed model. Obtained computation results provide the numerical evidence for partial coal impregnation, experimentally revealed by other researchers, clearly indicating the appearance of tar condensation zone in the area of parent coal that is adjacent to coal plastic layer. The progress in tar accumulation accompanying the softened stage layer migration towards an oven center as the process proceeds, was demonstrated. The applied approach allowed to illustrate the change in pressure distribution within the coal/coke bed, reproducing an effect of gas flow blockage on the parent coal side due to reduced permeability of both layers, that of softened coal and that occupied by condensed tar. Highlights: One-dimensional thermal and flow model of coal carbonization was developed. Phase transitions of moisture and tar mixture were taken into account. The zones of tar condensation within a coal bed were numerically identified. Used approach may be useful in predicting pressure change dynamics in a coke oven.